Speed Estimation of Moving Vehicle based on Input Images from a Smartphone Camera - Tukiran, Zarina; Aminuddin, Nuramin Fitri; Joret, Ariffuddin; Abdul Kadir, Herdawatie; Mohd Shah, Shaharil (Evolution in Electrical and Electronic Engineering, 2021)
Using a mobile smartphone camera, this work explored an alternative approach for estimating the speed of moving vehicles. A hardware prototype is developed to monitor the linear movement of vehicle, then the position of the vehicle is detected by using background subtraction as well as tracked using Gaussian Mixture Models (GMM). By comparing the pixel velocity and the measured speed of vehicle, the average pixel velocity for specific speed is determined. The initial findings show promising results to utilise smartphone technology for traffic monitoring application.